2017
DOI: 10.15446/rcs.v40n2.66385
|View full text |Cite
|
Sign up to set email alerts
|

Novas experiências, outros significados: repensando o trabalho no comércio popular

Abstract: En el artículo, tengo como propósito principal discutir las transformaciones del trabajo en el comercio popular en São Paulo, llevando en cuenta las recientes políticas de formalización y transición de estas actividades de las calles para las galerías. Busco discutir los efectos de estas transformaciones desde trayectorias sociales de trabajadores, demarcadas por nuevas experiencias de trabajo en el comercio popular y nuevos significados dados a la ocupación. En el contexto actual, podemos considerar que los a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Nas últimas décadas, contudo, e de maneira mais aguda nos últimos anos, o assalariamento formal tem deixado de significar uma possibilidade concreta de mobilidade social para muitas pessoas, bem como tem se enfraquecido o lugar de segurança e proteção social que ocupava na representação popular, sendo, para muitos, mais uma promessa do que uma realidade à qual tiveram acesso (Fischer, 2008;Cardoso, 2010). Consequentemente, esse "desencantamento da relação salarial" (Rangel, 2017), identificado em diversas pesquisas com trabalhadores do comércio popular (Gago, 2018;Rangel, 2019;Nahoum, 2020), tem tornado mais plausíveis a positivação do trabalho autônomo e informal e a elaboração de expectativas promissoras mesmo nessas atividades ainda estigmatizadas e cujo cotidiano de trabalho é atravessado pela precariedade e insegurança material e, não raro, física.…”
Section: A Gestão Empresarial Dos Mercados Popularesunclassified
“…Nas últimas décadas, contudo, e de maneira mais aguda nos últimos anos, o assalariamento formal tem deixado de significar uma possibilidade concreta de mobilidade social para muitas pessoas, bem como tem se enfraquecido o lugar de segurança e proteção social que ocupava na representação popular, sendo, para muitos, mais uma promessa do que uma realidade à qual tiveram acesso (Fischer, 2008;Cardoso, 2010). Consequentemente, esse "desencantamento da relação salarial" (Rangel, 2017), identificado em diversas pesquisas com trabalhadores do comércio popular (Gago, 2018;Rangel, 2019;Nahoum, 2020), tem tornado mais plausíveis a positivação do trabalho autônomo e informal e a elaboração de expectativas promissoras mesmo nessas atividades ainda estigmatizadas e cujo cotidiano de trabalho é atravessado pela precariedade e insegurança material e, não raro, física.…”
Section: A Gestão Empresarial Dos Mercados Popularesunclassified
“…It's a matter of sitting down and talking and reaching a common ground for this to materialize. (Daniel Ferrer Filho, trader at Feira da Madrugada -stenographic notes from the CPI, 8/8/2017) Currently, it is observed that work experiences in the popular commerce in Brazil have become more heterogeneous (Rangel;Araújo Filho, 2022), especially in a market of great importance like Brás and the Feirinha. This heterogeneity, driven by the transformations in the world of work in recent decades, further highlights the inadequacy of analyzing engagement in these activities solely focusing on "absences" (lack of education, qualifications, skills, opportunities).…”
Section: The Entrepreneurial Management Of Popular Marketsmentioning
confidence: 99%
“…Additionally, the sense of security and social protection that it once held in the popular imagination has weakened, becoming for many more of a promise than a reality they have access to (Fischer, 2008;Cardoso, 2010). Consequently, this "disenchantment with wage relations" (Rangel, 2017), as identified in various studies with workers in popular commerce (Gago, 2018;Rangel, 2021;Nahoun, 2020), has made the positive valuation of autonomous and informal work more plausible. It has also led to the formation of promising expectations, even in these stigmatized activities characterized by daily precarity and material, and often physical, insecurity.…”
Section: The Work In Popular Commerce Between the Image Of Poverty An...mentioning
confidence: 99%
“…However, studies have identified several changes in informal markets of different Brazilian regions over the past years. Researchers identified new worker profiles (Durães 2013;Rangel 2017) and changes to social statutes of such activities; once relegated almost exclusively to marginal positions, they are now recognized to be tied to large production and circulation chains (Rabossi 2004;Pinheiro-Machado 2011;Freire da Silva 2014).…”
Section: Introductionmentioning
confidence: 99%